HUBUNGAN TINGKAT STRESS DAN POLA KONSUMSI DENGAN KEJADIAN GASTRITIS DI PUSKESMAS PAKUAN BARU JAMBI - Merita Merita; Wilpi Inda Sapitri; Irawati Sukandar (Jurnal Akademika Baiturrahim Jambi, 2016)
Background: In the Indonesian incidenceof gastritis has a high prevalence. Gastritisgenerally occurs due to stomach acid is high or eating too many foods that are stimulatingwhom the food was spicy and sour. Therefore, this study aims to determine therelationship of stress and food pattern with the incidence ofgastritis in Primary Health Center of Pakuan Baru, Jambi City 2015.Methods: The research is a qualitative with case control method. This research was conducted on June 26 th - July 1st, 2015at the health center of Pakuan Baru Jambi. The sampling technique used waspurposive sampling with a sample of 72 people. Data were collected by interview withusing a questionnaire, collected data analyzed by univariate and bivariate (chi-square).Result: The chi-square analysis showed that there is asignificant relationship between stress and the incidence of gastritis (p value = 0.000, OR = 9.416), between the pood pattern witn to the incidence of gastritis (p value = 0.000, OR = 38.5).Conclusion: There is relationship stress and food pattern withthe incidence of gastritis in Primary Health Center of Pakuan Baru, Jambi City 2015.Keywords : Stress, Food Patterns, Gastritis